Differential Diagnosis of Kleine-Levin Syndrome - Millichap, J. Gordon (Pediatr Neurol Briefs, 2015)
Investigators at Pitie-Salpetriere and Robert Debre Hospitals, and other centers in France, evaluated consecutive patients referred for suspected Kleine-Levin (KLS) syndrome, detailed differential diagnoses, and examined characteristics of patients with prolonged (>30 days) episodes.